THE EFFECT OF HEAT TREATMENT AND SURFACE ANODIZATION ON FRICTION AND WEAR COEFFICIENT OF ALUMINIUM 2024 USING PIN ON DISK METHOD - Tiya Khairina Izzati; Aristo Nugraha Putra; Budi Hartono Setiamarga; Yorinah Sarah Francoise Lantang (Metalurgi, 2022)
The use of aluminum alloys as a material for engineering components that rub against each other is increasing, so it is important to know the friction characteristics of these aluminum alloys.  In this study, Aluminum 2024 was given heat treatment with variation in aging time and anodization. Then, the wear and friction coefficient tests were carried out using a pin tool on the disc. The effect of aging time and surface anodization on wear tests are carried out to determine the amount of wear and the coefficient of friction test is carried out to determine the coefficient of friction of the material when it rubs against a pin made of AISI 52100 Steel. The coefficient of friction test is carried out by adding lubrication as a parameter. The test results showed that the aluminum material given heat treatment had better resistance than that which was not heat treated. This is because the heat treatment creates precipitates that can increase the aluminum's hardness and wear resistance. Whereas for anodized specimens, the alumina layer can act as an abrasive grain when given a high enough friction and load continuously, so the wear testing mode changes from dry sliding wear to three body abrasive wear and decreased wear resistance. From the friction coefficient test results, the aging time affects the hardness of the aluminum alloy, which leads to the value of the coefficient of friction. The harder the sample surface, the smaller the coefficient of friction obtained. Furthermore, applying lubricant to the sample will also decrease the value of the friction coefficient of the sample. Lubricating oil will provide a more significant reduction in friction coefficient than air. Finally, the anodizing surface on the sample will act as a lubricant reservoir when it occurs.